2014
DOI: 10.1007/s00339-014-8860-y
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the carrier concentration in CdSe crystals from the effective infrared absorption coefficient measured by means of the photothermal infrared radiometry

Abstract: In this paper, a non-contact method that allows to determine the carrier concentration in CdSe crystals is presented. The method relies on the measurement of the effective infrared absorption coefficient by means of the photothermal infrared radiometry (PTR). In order to obtain the effective infrared absorption coefficient and thermal diffusivity, the frequency characteristics of the PTR signal were analyzed in the frame of a one-dimensional heat transport model for infrared semitransparent crystals. The carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Furthermore, the carrier contribution can be also considered negligible since we are dealing with a semiconductor of small direct band gap (0.91 eV) [19][20][21]. In such a situation, the recombination lifetime is very short (~10 s ns if the analysis is performed by the use of ThWs determined in [18]) and the carrier contribution can be neglected in low and intermediate frequencies range [20,21]. Additionally, it was demonstrated that, the conductivity of CuFeInTe 3 material presents metallic behavior [19].…”
Section: Photodeflection Signalmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the carrier contribution can be also considered negligible since we are dealing with a semiconductor of small direct band gap (0.91 eV) [19][20][21]. In such a situation, the recombination lifetime is very short (~10 s ns if the analysis is performed by the use of ThWs determined in [18]) and the carrier contribution can be neglected in low and intermediate frequencies range [20,21]. Additionally, it was demonstrated that, the conductivity of CuFeInTe 3 material presents metallic behavior [19].…”
Section: Photodeflection Signalmentioning
confidence: 99%
“…The temperature rise of the sample caused by illumination by the pump beam is a fraction of Kelvin, thus, both the heat convection and radiation can be considered negligible. Furthermore, the carrier contribution can be also considered negligible since we are dealing with a semiconductor of small direct band gap (0.91 eV) [19][20][21]. In such a situation, the recombination lifetime is very short (~10 s ns if the analysis is performed by the use of ThWs determined in [18]) and the carrier contribution can be neglected in low and intermediate frequencies range [20,21].…”
Section: Photodeflection Signalmentioning
confidence: 99%
“…Photothermal methods are noncontact and very suitable methods for thermal characterization of semiconductors [11][12][13]. Thus, the thermal diffusivity was determined by a photothermal method with mirage detection.…”
Section: Determination Of Thermal Diffusivitymentioning
confidence: 99%
“…Experimental methods which provide simultaneous information about both thermal and infrared properties are thus very attractive. Among them, the modulated photothermal infrared radiometry (PTR) is a noncontact method for measuring thermal, infrared and electronic transport properties of semiconductor species [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%